PENGARUH PENGETAHUAN AKSEPTOR DENGAN PEMILIHAN KONTRASEPSI IMPLANT - Windarti, Yunik (Universitas Nahdlatul Ulama Surabaya, 2015)
The influence of acceptor?s knowledge with the selection of implant contraception. Implant is one of hormone contraceptive methode with high effectiveness. But, know fact that there were acceptors refused to use implant. The caused factor is the less off acceptors knowledge about implant. Therefore, this research was influence of acceptor?s knowledge with the selection of implant contraception. The type of this research was analytic by non probability. The po samplingpulation involved 42 acceptors of hormonal contraceptive who attended on may at BPM Kusmawati Surabaya. 38 respondents were taken as the samples using accidental sampling technique. The independent variable was knowledge where as, the dependent one was the selection. Questionnaires was used to collect the data. Analyzed by using Mann-Whitney test with the significance level ? = 0,05. The result of this research showed that most of respondents (60,5%) had less knowledge and almost all respondents (89,5%) did not use implant. Furthermore, the statistic test has obtarned p = 0,039 < ? = 0,05. So H0 was refused that there was influence of acceptor?s knowledge with the selection of implant. The research concluded that the less of acceptors knowledge about implant. The used of this contraceptive is vower. Hence, the health workers should improve the counselling and implant extension to people.